Regional peculiarities of the Zrubna/Timber-grave culture tribes’ calendar system - Zabavin, Viachesiav; Nebrat, Serhii (Skhid, 2023)
The article presents the results of the study on the burial of the Zrubna/Timber-Grave culture (Late Bronze Age) from the mound near the village of Komyshuvate in the North Azov Area in the south of Donetsk Region of Ukraine. The article deals with issues related to some peculiarities of the material and spiritual culture of the ancient population of the Azov steppes, their social organization and funeral rites. Ceramic vessels are the most common category of equipment in the funerary inventory of the Zrubna/Timber-grave culture graves. Finds of pottery with extraordinary ornaments, which researchers interpret as pictograms, proto-literacy, and plot drawings, have always been of particular interest. The calendar ornamentation on the pots of the Zrubna/Timber-grave culture deserves special attention. The pot with the ornamentation, which, according to the authors, was of a calendar nature, comes from burial 1 of barrow 4 of the Komyshuvate cemetery. A detailed analysis of the ornamentation on the pot from this burial allowed us to suggest that the cyclic composition depicted on the ceramic vessel records recurring time periods that were important to the ancient population. Perhaps the ornament also reflects the regional peculiarities of the calendar system of the Zrubna/Timber-grave culture tribes: annual and lunar cycles with the time of transition from the old to the new year.